A transient ultraluminous X-ray source in NGC 55. Issue 4 (22nd July 2022) - Robba, A; Pinto, C; Pintore, F; Rodriguez, G; Ambrosi, E; Barra, F; Cusumano, G; D'Aì, A; Del Santo, M; Kosec, P; Marino, A; Middleton, M; et al.
ABSTRACT: Ultraluminous X-ray sources (ULXs) are a class of accreting compact objects with X-ray luminosities above 10 39  erg s −1 . The average number of ULXs per galaxy is still not well-constrained, especially given the uncertainty on the fraction of ULX transients. Here, we report the identification of a new transient ULX in the galaxy NGC 55 (which we label as ULX-2), thanks to recent XMM–Newton and the Neil Gehrels Swift Observatory observations. This object was previously classified as a transient X-ray source with a luminosity around a few 10 38  erg s −1 in a 2010 XMM–Newton observation. Thanks to new and deeper observations (∼130 ks each), we show that the source reaches a luminosity peak >1.6 × 10 39  erg s −1 . The X-ray spectrum of ULX-2 is much softer than in previous observations and fits in the class of soft ULXs. It can be well-described using a model with two thermal components, as often found in ULXs. The time-scales of the X-ray variability are of the order of a month and are likely driven by small changes in the accretion rate or due to super-orbital modulations, attributed to precession of the accretion disc, which is similar to other ULXs.